Impact of restrictive lung disorder on cardiovascular mortality in a general population: The Yamagata (Takahata) study. (15th August 2017) - Honda, Yuki; Watanabe, Tetsu; Shibata, Yoko; Otaki, Yoichiro; Kadowaki, Shinpei; Narumi, Taro; Takahashi, Tetsuya; Kinoshita, Daisuke; Yokoyama, Miyuki; Nishiyama, Satoshi; Takahashi, Hiroki; Arimoto, Takanori; et al.
Abstract: Background: Obstructive lung disorder (OLD) is known to be associated with cardiovascular disease. However, the impact of restrictive lung disorder (RLD) on cardiovascular mortality has not been fully investigated in the apparently healthy general population. Objectives: To clarify whether RLD is associated with cardiovascular mortality in the general population. Methods and results: This community-based cohort study included 3247 subjects who participated in an annual health check in Takahata. We performed spirometry in registered subjects and found that 194 (6%) had RLD, 262 (8%) had OLD, and 73 (2%) had RLD and OLD (Mixed). During a 10-year follow-up, there were 210 deaths, including 57 cardiovascular deaths. Cardiovascular mortality of subjects with RLD was significantly higher than that of subjects with normal lung function. Although the subjects with RLD were younger, comprised fewer smokers, and were more likely to be female than those with OLD, cardiovascular mortality of subjects with RLD was comparable to that of subjects with OLD. Subjects with RLD had a higher prevalence of atrial fibrillation (AF) than those with OLD, and the prevalence of AF was increased with advanced severity of RLD. Multivariate Cox proportional hazard analysis revealed that RLD was an independent predictor of cardiovascular death (hazard ratio 2.61, 95% confidence interval, 1.22–5.21) after adjustment for confounders, but OLD was not. The net reclassification improvement and integrated discrimination improvement were significantly increased by the addition of RLD to conventional cardiovascular risk factors. Conclusion: The presence of RLD was associated with cardiovascular mortality in the general population.